The effects of tamarind seed extract against muscle, liver and renal alterations induced envenomation with King Cobra venom - Al-Ani, Imad Matloub Dally; Ismail, Soraya; Maung, Khin M.; Oothuman, Pakeer (2015)
Tamarind (Tamarindus indica) has been used as medical plant for treating many human and animal diseases and widely used as a traditional herbal medicine for the treatment of snake bites. The objective of the study is to investigate whether tamarind seed extract have neutralization activity on adverse histological reaction against venoms of the King Cobra. Twenty healthy mature male mice were randomly divided into 4 groups with 5 mice in each. The control group was injected with 1 ml of normal saline. The second group was injected subcutaneously with a single dose of 24.96µg/20g King Cobra venom (KCV) solution. The third group was injected with the same dose of KCV solution and 10mg/20g of Tamarind seed extract (TSE). The fourth group was injected with the same dose of KCV solution and 15mg/20g TSE solution. The animals were sacrificed after 24 hours of injection of the solution. Fragments of muscle, kidney and liver were fixed in 10% neutral buffered formalin, and processed for light microscopical studies. The result showed that TSE reduced the histopathological changes induced by the King Cobra venom in the muscles, livers and kidneys and the improvement was proportional to the applied dose of the TSE indicating that tamarind seed extract prevents adverse histological changes in the muscle, liver and kidney.